Concerns, difficulties and decision making of future teachers who interned and taught mathematics at Youth and Adult Education - Alana Silva dos Santos; Clebison Pereira dos Santos; Iago Ailton do Vale Saturnino dos Santos; Lilian Aragão da Silva (Universidade Federal do Oeste da Bahia, 2021)
This work aims to report the experiences of future teachers who taught mathematics in Youth and Adult Education (EJA) classes. In particular, these experiences are related to the concerns, difficulties and decision making of these subjects when they developed the observation and conducting internship at EJA. As a result, we report concerns, difficulties and decision-making by future teachers that reflected aspects of a methodological, pedagogical or didactic nature, as a result of problems inherent to EJA, the lack of public policies and institutional silence. In addition, we report the difficulties of students of EJA, in relation to the discipline of mathematics, which were faced by future teachers through decision making that resulted in the way of conducting or mediating the class and the use of didactic strategies to teach mathematics.